Case Report: A case series of Lhermitte–Duclos disease with surgical intervention - Chen, Ziyang; Guo, Min; Li, Xingke; Lin, Cheng; Feng, Guili; Zhou, Jianzhi; Li, Hainan; Chen, Baijie; Liu, Lirong; Cai, Linbo; Wang, Lei; Ouyang, Hui; et al. (Frontiers in Oncology, 2025)
BackgroundLhermitte–Duclos disease (LDD) is a rare dysplastic cerebellar gangliocytoma often associated with Cowden syndrome and phosphatase and tensin homolog (PTEN) alterations. We report a three-case series focusing on imaging, histopathology, PTEN testing, surgical decision-making, and outcomes.MethodWe retrospectively identified three adults with LDD who underwent standardized preoperative imaging [including magnetic resonance spectroscopy (MRS) and perfusion when feasible], surgery, and structured follow-up with Karnofsky Performance Status (KPS). PTEN assessment included immunohistochemistry and/or genetic testing where available.ResultsAll patients in this case series were women (18–53 years). Two underwent subtotal resection and one underwent gross total resection. Characteristic “tiger-striped” magnetic resonance imaging (MRI) appearance was present in all cases. Histopathology showed thickened molecular layer, loss of Purkinje cells, and hypertrophic ganglion-like neurons. One patient required unplanned posterior fossa decompression due to severe postoperative edema. At 6 months, two patients improved functionally while one had poor neurological outcome. PTEN testing supported the association with PTEN hamartoma tumor syndrome in one case.ConclusionPTEN evaluation should be considered in adults with LDD, especially when clinical features suggest Cowden syndrome. Surgical management should balance extent of resection with preservation of venous outflow and cerebellar function. Non-surgical strategies [observation, stereotactic radiotherapy, and exploratory mechanistic target of rapamycin (mTOR) inhibition] may be an option in selected scenarios.LimitationsThis single-center retrospective series is limited by its small sample size and variable follow-up imaging.